The contribution of antibiotic resistance mechanisms in clinical Burkholderia cepacia complex isolates: an emphasis on efflux pump activity. - Sung-Pin Tseng (PLoS ONE, 2014)
Due to the limited information of the contribution of various antibiotic resistance mechanisms in clinical Burkholderia cepacia complex isolates, Antibiotic resistance mechanisms, including integron analysis, identification of quinolone resistance-determining region mutations, measurement of efflux pump activity, and sequence analysis of efflux pump regulators, were investigated in 66 clinical B. cepacia complex isolates. Species were identified via recA-RFLP and MALDI-TOF. Four genomovars were identified by recA-RFLP. B. cenocepacia (genomovar III) was the most prevalent genomovar (90.1%). Most isolates (60/66, 90.9%) were correctly identified by MALDI-TOF analysis. Clonal relatedness determined by PFGE analysis revealed 30 pulsotypes, including two major pulsotypes that comprised 22.7% and 18.2% of the isolates, respectively. Seventeen (25.8%) isolates harboured class 1 integron with various combinations of resistance genes. Among six levofloxacin-resistant isolates, five had single-base substitutions in the gyrA gene and three demonstrated efflux pump activities. Among the 42 isolates exhibiting resistance to at least one antimicrobial agent, 94.4% ceftazidime-resistant isolates (17/18) and 72.7% chloramphenicol-resistant isolates (16/22) demonstrated efflux pump activity. Quantitation of efflux pump RNA level and sequence analysis revealed that over-expression of the RND-3 efflux pump was attributable to specific mutations in the RND-3 efflux pump regulator gene. In conclusion, high-level expression of efflux pumps is prevalent in B. cepacia complex isolates. Mutations in the RND-3 efflux pump regulator gene are the major cause of efflux pump activity, resulting in the resistance to antibiotics in clinical B. cepacia complex isolates.